Implementing Heart-Based Education from Ibn Qayyim al-Jawziyyah’s Perspective to Develop Students’ Character at MAN 1 Medan - Rabiatul Adawiyah; Syamsu Nahar; Nurussakinah (GHAITSA : Islamic Education Journal, 2026)
This research is motivated by the increasing crisis of student character in the digital era, which is characterized by a decline in students' ethics, discipline, and moral awareness. This condition shows the importance of an educational approach that is not only oriented towards academic aspects, but also on the spiritual and character development of students. This study aims to analyze the implementation of education with the heart from the perspective of Ibn Qayyim al-Jawziyyah in the formation of student character at MAN 1 Medan, identify the forms of application of qalbiyah educational values, and analyze the supporting factors and obstacles in its implementation. This study uses a qualitative approach, data obtained through observation, in-depth interviews, and documentation of the principal, teachers, and students. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions, while data validity is carried out through triangulation of sources and techniques. The results of the study indicate that the implementation of education with the heart at MAN 1 Medan is carried out through strengthening the value of monotheism, habituation of worship, teacher role models, a compassionate approach, and humanistic communication in the learning process. This approach has a positive impact on student character development, such as increased discipline, responsibility, manners, social awareness, and spiritual awareness. This study also shows that Ibn Qayyim al-Jawziyyah's educational theories regarding the heart (qalb), tazkiyat al-nafs (self-control), and uswah hasanah (good character) remain relevant in the context of modern education. This research contributes to the development of spiritual-based Islamic education and character education studies through the integration of classical Islamic educational thought with contemporary educational practices.